Evaluation of Industrial Training Learning Experiences - Ling, Jen Hua; Leong, Wen Kam (Indonesian Journal of Education and Social Sciences, 2025)
Industrial training (IT) is a critical component of engineering education, offering students practical experience and linking academic theory with professional practice. However, its effectiveness in preparing students for the workforce has not been thoroughly examined. This study assesses IT by evaluating its alignment with the standards of the Engineering Accreditation Council (EAC) and collecting student feedback through surveys with 23 students. The findings reveal that the IT met all 11 EAC requirements. Survey results indicate that all students gained valuable real-world insights, with 95.7% reporting improved technical skills and 91.3% noting enhanced soft skills. Despite these positive outcomes, several challenges were identified, including subjective student feedback, inconsistent industrial exposure, limited training duration, and difficulties in monitoring and assessment. These findings highlight areas for improvement in both the curriculum and the IT, suggesting future efforts should focus on refining industrial exposure, enhancing assessment methods, and fostering stronger collaboration with industry partners.